Effectiveness Of Entrepreneurship Education and Demographic Environment on Entrepreneurial Interest Through Entrepreneurial Attitude as An Intervening Variable - Ahmad Zainudin; Nasikh, Nasikh; Sumanto, Agus (Perkumpulan Dosen Program Hibah Indonesia, 2023)
This research aims to determine the Effectiveness Of Entrepreneurship Education and Demographic Environment on Entrepreneurial Interest Through Entrepreneurial Attitude as An Intervening Variable. It is time for the younger generation to change their perspective, do not just think about becoming an employee after graduating from college, let alone a public servant, becoming an entrepreneur needs to be considered as an option. The hope of being accepted into the world of work is certainly not a mistake, but it cannot be denied that job opportunities are very limited and not directly proportional. This study uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the hypothesis given. This study uses Google Forms to collect data on private vocational students in Mojokerto Regency. Respondents in this study were 319 respondents who were used as research objects. The results showed that entrepreneurship education cannot explain entrepreneurial attitudes. Likewise, the demographic environment variable cannot explain entrepreneurial interest. Furthermore, the demographic environment will have more influence on entrepreneurial interest, if reinforced by entrepreneurial attitude as a mediator variable. While entrepreneurship education will not have a greater influence on entrepreneurial interest, although strengthened by entrepreneurial attitude as a mediator variable.